DIVERSITY OF MEDICINAL PLANT RESOURCES AND USE VALUES AT TAN PHU PROTECTIVE FORESTS, DONG NAI PROVINCE, VIETNAM - Thi Ha, Nguyen; Viet Hung, Dang; Thanh Duy, Le; Van Hop, Nguyen; Thi Danh Lam, Nguyen (Journal of Forestry Science and Technology, 2022)
The article presents the research results on medicinal plant resources at Tan Phu Protective Forests, Dong Nai Province. Initially, 351 plant species have been identified for medicinal use, belonging to 83 families, 3 plant divisions; in which: Pinophyta has 1 species belonging to 1 family; Polypodiophyta has 11 species belonging to 4 families; Magnoliophyta has 339 species belonging to 78 families. The life form is very diverse with the woody group having the highest number of species 152 species (accounting for 43.3%), the group of herbs having 73 species (20.8%), the group of shrubs, having 72 species (20.5%); The liana has 40 species (11.4%) and the epiphytes has the least with 14 species (4.0%), respectively. Medicinal plants are mainly used to treat groups of pimples, rashes, inflammation with 155 species (accounting for 44.16%); the group used to treat colds and fever with 112 species (accounting for 31.9%); group used to treat dysentery, diarrhea with 107 species (30.5%); group used to treat low and painful anesthesia with 105 species (29.9%); in the digestive system with 104 species (29.63%), respectively. The most commonly used treatment is pounding for topical use and excellent for internal use. Recorded 07 species in Group IIA in Decree 06/2019/ND-CP; 06 species in the Vietnam Red Data Book (2007): 03 species classified as Vulnerable - VU; 03 species classified as Endangered - EN. The medicinal resources here are being over-exploited, so it is necessary to have measures for conservation and development.